Pola Bakteri dan Resistensi Antibiotik pada Pasien Sepsis di Intensive Care Unit (ICU) RSUD Arifin Achmad Provinsi Riau Periode 1 Januari – 31 Desember 2017 - Dicky Septian Wijaksana; Novita Anggraeni; Rita Endriani (Fakultas Kedokteran Universitas Riau, 2019)
Sepsis is life-threatening condition caused by bacteria. Sepsis patient usually treated in ICU with antibiotic as treatment. Irrationally antibiotic usage can lead to antibiotics resistance which increased morbidity and mortality This study aimed to know the characteristic of sepsis patients, specimen identification, bacteria analysis, and antibiotic resistance of sepsis patient in Intensive Care Unit (ICU). The source of data were from medical record including age, gender, culture specimen, bacteria culture test and result of antibiotic resistance test. Result showed that27 of samples, there were 51,85% male and 48,15% female patient with most common age group was >65 years old (25,93%). Total amount of specimen that had pathogenic bacteria was 37, (67,57% sputum cultures and 18,92% blood cultures). 37 of samples found to be gram negative bacteria and highest number was A.baumanii (37,85%). Antibiotic resistance test showed that sepsis-causing bacteria has highest resistance to ampicillin (100%) and most sensitive to amikacin (72,98%) and tigecyclin (51,36%).